The Effect of Aqueous Extract of Quercus infectoria Plant on Pap E gene Expression of Uropathogenic Escherichia coli - Ammar Jawad Kadhim; Hassan Majeed Rasheed (Institute of Medico-legal Publications Pvt Ltd, 2021)
One hundred twelve urine samples were collected from Baghdad hospitals and examined by differentidentification techniques. Seventy isolates (62.5%) were diagnosed as Escherichia coli after microscopicand cultural identifications. The result of PCR product electrophoresis on the isolates showed that thirteenisolates (18.57%) have Pap E gene which are uropathogenic E. coli. Antibiotic susceptibility test was done,and four high resistant strains were mixed with aqueous extract of Quercus infectoria plant in 96 well ELISAplate and incubated for different times. After 0, 6, and 12 hr. of incubation, the effect of the plant extract onthe bacterial growth was determined by ELISA reader, and the effect on the expression of Pap E gene wasexamined by real-time PCR. The results were showed that the higher effect of the extract was on the E10strain growth that dropped from 3.184 at zero time of incubation to 2.378 and 2.281 after 6, and 12 hrs. ofincubation respectively. Also, shown a downregulation in the expression of Pap E gene of the isolates atdifferent times of incubation. The E10 strain shows decrease in the fold from 1 before the treatment with theextract to 0.076 at zero time of incubation with the extract, after 6 and 12 hrs. of incubation it shows a totaldown-regulation of the gene.